Corporate Culture’s Effect on Corporate Sustainability: Exploring the Mediating Effect of Innovation Capability in Foreign Companies Operating in Ghana - Francis Osei; Beverley Wilson-Wünsch; Collins Kankam-Kwarteng; Alfred Owusu (International Journal of Entrepreneurship, Business, and Creative Economy, 2025)
The issue of sustainable development poses a significant challenge for foreign enterprises, especially in volatile markets such as Ghana, where these firms face unique obstacles in aligning their corporate culture with sustainability goals. Drawing upon the literature on sustainable corporate development and adopting the resource-based view, this research addresses a gap in understanding how corporate flexibility and control culture influence corporate sustainable performance through the stimulation of innovation capabilities, specifically within the context of foreign enterprises. Data were collected from 152 foreign companies operating in Ghana, and Structural Equation Modeling was conducted using Smart PLS version 3.0 and SPSS version 24. The questionnaire was based on the existing literature. The findings of this study indicate that both flexibility and control cultures have a significant influence on innovative capability, yet they do not directly affect corporate sustainable performance. The research reveals that innovation capability acts as a complete mediator between flexibility and control culture and sustainable corporate performance. This research contributes to the theoretical literature on sustainable corporate performance and offers valuable managerial insights for foreign firms in Ghana, guiding them on how to navigate and achieve sustainable growth through strategic corporate culture.